Acetyltransferase p300 inhibitor reverses hypertension‐induced cardiac fibrosis. Issue 4 (1st February 2019) - Rai, Rahul; Sun, Tianjiao; Ramirez, Veronica; Lux, Elizabeth; Eren, Mesut; Vaughan, Douglas E.; Ghosh, Asish K.
Abstract: Epigenetic dysregulation plays a crucial role in cardiovascular diseases. Previously, we reported that acetyltransferase p300 (ATp300) inhibitor L002 prevents hypertension‐induced cardiac hypertrophy and fibrosis in a murine model. In this short communication, we show that treatment of hypertensive mice with ATp300‐specific small molecule inhibitor L002 or C646 reverses hypertension‐induced left ventricular hypertrophy, cardiac fibrosis and diastolic dysfunction, without reducing elevated blood pressures. Biochemically, treatment with L002 and C646 also reverse hypertension‐induced histone acetylation and myofibroblast differentiation in murine ventricles. Our results confirm and extend the role of ATp300, a major epigenetic regulator, in the pathobiology of cardiac hypertrophy and fibrosis. Most importantly, we identify the efficacies of ATp300 inhibitors C646 and L002 in reversing hypertension‐induced cardiac hypertrophy and fibrosis, and discover new anti‐hypertrophic and anti‐fibrotic candidates.